Relationship Between Working Mothers towards Exclusive Breastfeeding in Bunda Maternity Clinic Surabaya - Devina Callista Ayungga; Risa Etika; Eighty Mardiyan Kurniawati (Humanistic Network for Science and Technology (HNST), 2020)
Background: The percentage of infants who receive exclusive breastfeeding in Indonesia can be much higher. There are many factors including working mothers. Aim: To find out if there is a significant relationship between working mothers towards exclusive breastfeeding. Methods: This study was an analytic observational study done using the data acquired from a questionnaire given to mothers who come to Bunda Maternity Clinic in Surabaya. Data was then analysed statistically using Chi square test. Result: Out of 20 working mothers, 6 (30%) of them exclusively breastfed their infants while the rest did not. Out of 37 non-working mothers, 28 (76%) of them exclusively breastfed their infants. A p-value of p